ANALISIS PEMBENARAN INTERNAL (INTERNAL JUSTIFICATION) PADA TINDAKAN MENYONTEK DI KALANGAN MAHASISWA - Idawati, Kurnia; Fitriani, Nurul; Sulaeman, Karina Adinda (Universitas Majalengka, 2023)
The aim of this research is to reveal justifications the students made when they cheated on their academic tasks as well as the analysis in the aspects of educational psychology and collectivism culture on those justifications. The research method is qualitative interpretive on quantitative data obtained through a written survey. From the research results, various motives or reasons as justifications for the students to cheat can be grouped into two categories, namely the